Estratégias de enfrentamento utilizadas por trabalhadores da indústria têxtil frente ao trabalho repetitivo - Alana Pires Dale (2022)
The textile industry is undoubtedly an important economic activity, among those existing in the Brazilian market, a great generator of jobs and revenue. However the required assignments in this environment can negatively affect the health of their workers, for example performing repetitive movements for a long period of time, typical characteristics of industrial jobs that use machines in their production process. To try to prevent from the obstacles encountered in carrying out activities, a great number of works are forced to use alternatives to escape, to appease and/or face such risks. It is from the knowledge of these situations that we aim to identify the confrontation strategies used by workers in a textile industry against repetitive work. The research was realized with workers in a textile industry, from the countryside of Brazil who perform repetitive movements in their daily workday. The case study associated methodological resources of the The Ergonomic Work Analysis (EWA) to the assumptions and concepts of Ergological Work Approach. In a first exploratory phase, the research problem was approached by gathering information about the company and its workers. In a second moment the investigation deepened the issue through individual semi-structured interviews with nine workers, observing them in a work situation. In the work situations selected for study, we verified work risks, as performing repetitive movements, such as forced and inappropriate posture, lifting and weight transportation, intense noise, long time standing, excess cotton dust in the air, risks of machine accidents. Focusing specifically on performing repetitive movements, we discovered as confrontation strategies the reduction of the pace and intensity of work, the acquisition of knowledge about machines and materials, pain medication ingestion, avoiding mistakes that subsequent must be repaired in even more strenuous activities, stretching before and during work, knowledges about how to transport the boxes, make tin fold, among others. Thus we were able to validate some assumptions of Ergological Work Approach that subjects are not mere executors of tasks, but rather possessors of knowledge, desires, values, intelligence, stories, and this configures the ways of how they perform the activities. Highlighting three key points: the relationship between strategies, renormalizations and health; the multicausal risks of illness (physical, organizational) and; the non-absolute positivity of the consequences of the use of coping strategies, which aim to ensure health.